NSAID GASTROPATHY: CHANGES OVER 12 YEARS - A E Karateev (Научно-практическая ревматология)
Nonsteroidal anti-inflammatory drugs (NSAIDs) are the most popular medications to relieve the symptoms of rheumatoid arthritis (RA). However, NSAIDs can cause serious gastrointestinal, cardiovascular, and renal complications. To take into account risk factors and to use safer NSAIDs and gastroprotectors allow the frequency of gastrointestinal tract (GIT) complications to be reduced. These preventive methods have been extensively used in recent years. Objective: to estimate the time course of changes in the incidence of upper GIT pathology in patients with RA in 1995-1996 and 2008-2009 and to identify the factors influencing these changes. Subjects and methods. The results of endocopic studies were analyzed in all RA patients aged over 18 years, who had been admitted to the Clinic of the Research Institute of Rheumatology, Russian Academy of Medical Sciences, and undergone this procedure in 1995-1996 (n = 984; Group 1) and in 2008-2009 (n = 1018; Group 2). In Groups 1 and 2, the patients' gender and age did not differ: women were 90.3 and 89.0% and the mean age was 48.2±15.6 and 44.1±16.3 years, respectively. NSAIDs were taken by all the patients in Group 1 and most (81.9%) of those in Group 2. In the 1990s, all the patients used nonselective NSAIDs; following 12 years, 61.4% received selective NSAIDs. Significantly more patients in Group 2 took glucocorticoids (37.6 and 52.6%) and cytotoxic agents (21.3 and 56.5%) (p < 0.001). Many patients had risk factors: an ulcer history in 18.7 and 20.9%, age over 65 years in 13.8% and 12.0%, respectively; in Group 2, 6.3% of the patients took low-dose aspirin (unknown percent in Group 1). In Group 2, 8.7% of the patients used proton pump inhibitors (PPIs). In the 1990s, the latter were not used to prevent NSAID gastropathy yet. Results. Endoscopic ulcers were found 2.5 times more frequently in Group 1 than in Group 2: 15.3 and 6.5%, respectively (p < 0.001). This pathology was detected more often in the presence of risk factors. For example, among Group 1 and 2 patients having an ulcer history, ulcers were identified in 33.2 and 12.7%; among the subjects over 65 years of age, these were in 20.5 and 9.7%, respectively. In Group 2 patients who had received aspirin, ulcers occurred 1.5 times more frequently than those in the whole group (9.7%). In all cases, the difference was statistically significant (p < 0.05). Erosive esophagitis was detected only in a small number of patients with RA. It was observed only in 4 (0.4%) and 21 (2.1%) patients in Group 1 and 2, respectively (p = 0.038). Discussion. The rate of NSAID gastropathy in RA declined. This resulted from more active disease-modifying therapy that permitted a reduction in the need for NSAIDs, from the use of safer NSAIDs, such as aceclofenac, meloxicam, nimesulide, and coxibs, and from that of PPIs. At the same time, there was an increase in the frequency of esophageal complications. This trend requires further investigation.